Effects of Xingnaojing Injection on Adenosinergic Transmission and Orexin Signaling in Lateral Hypothalamus of Ethanol-Induced Coma Rats. (27th June 2019) - Chen, Xiao-Tong; Wang, Xiao-Ge; Xie, Li-Yuan; Huang, Jia-Wen; Zhao, Wei; Wang, Qi; Yao, Li-Mei; Li, Wei-Rong
Abstract : Acute alcohol exposure induces unconscious condition such as coma whose main physical manifestation is the loss of righting reflex (LORR). Xingnaojing Injection (XNJI), which came from Chinese classic formula An Gong Niu Huang Pill, is widely used for consciousness disorders in China, such as coma. Although XNJI efficiently shortened the duration of LORR induced by acute ethanol, it remains unknown how XNJI acts on ethanol-induced coma (EIC). We performed experiments to examine the effects of XNJI on orexin and adenosine (AD) signaling in the lateral hypothalamic area (LHA) in EIC rats. Results showed that XNJI reduced the duration of LORR, which implied that XNJI promotes recovery form coma. Microdialysis data indicated that acute ethanol significantly increased AD release in the LHA but had no effect on orexin A levels. The qPCR results displayed a significant reduction in the Orexin-1 receptors (OX1 R) expression with a concomitant increase in the A1 receptor (A1 R) and equilibrative nucleoside transporter type 1 (ENT1) expression in EIC rats. In contrast, XNJI reduced the extracellular AD levels but orexin A levels remained unaffected. XNJI also counteracted the downregulation of the OX1 R expression and upregulation of A1 R and ENT1 expression caused by EIC. As for ADK expression, XNJI but not ethanol, displayed an upregulation in the LHA in EIC rats. Based on these results, we suggest that XNJI promotes arousal by inhibiting adenosine neurotransmission via reducing AD level and the expression of A1 R and ENT1.